Spatial averaging-effects on turbulence measured by a continuous-wave coherent lidar - Mikael Sjöholm; Torben Mikkelsen; Jakob Mann; Karen Enevoldsen; Michael Courtney (Meteorologische Zeitschrift, 2009)
The influence of spatial volume averaging of a focused continuous-wave coherent Doppler lidar on observed wind turbulence in the atmospheric surface layer is described and analysed. For the first time, comparisons of lidar-measured turbulent spectra with spectra simultaneously obtained from a mast-mounted sonic anemometer at 78 meters height over homogeneous terrain at the test station for large wind turbines at Høvsøre in Western Jutland, Denmark are presented for various backscattering and cloud conditions. Good agreement is found between lidar-measured spectra and spectra predicted by applying a theoretical lidar sampling filter to the three-dimensional turbulence structure.